Childhood motocross truncal injuries: high-velocity, focal force to the chest and abdomen. Issue 6 (19th November 2012) - Kennedy, Raelene D; Potter, D Dean; Osborn, John B; Zietlow, Scott; Zarroug, Abdalla E; Moir, Christopher R; Ishitani, Michael B; McIntosh, Amy
Abstract : Objectives: To review the need for operative intervention and critical care services for motocross truncal injuries in children. Design cohort: Retrospective review of patients identified via the hospital trauma registry. Setting: Our Level 1 Pediatric Trauma Center serves five motocross tracks. These patients require frequent medical care for injuries. Participants: All patients ≤17 years of age with truncal injuries sustained during motocross activities, between 2000 and 2011, were identified through the trauma registry. Primary and secondary outcome measures: Operative intervention, intensive care unit (ICU) admission, length of stay, morbidity and demographics were reviewed. Results: Motocross injured 162 children. Thirty (18.5%) were thoracic or abdominal injuries. Operative intervention was required in eight (27%) patients. Mean injury severity score (ISS) was 11.8. ICU admission was required in 50% and average hospital length of stay was 4.1 days. The most common injuries include pulmonary contusion, pneumothorax, spleen and liver lacerations. 13% of subjects suffered truncal injury from motocross on more than one occasion. Conclusions: Paediatric motocross-related truncal injuries are significant. Surgical intervention is required in 27% of patients. The lower ISS incurred from motocross combined with high surgical and ICU admission rates suggests focal high-impact injuries to the chest and abdomen. Despite significant injury, 13% of motocross patients suffer recurrent injuries. Parents and children need injury prevention education.